STRATEGIES OF SELF-REGULATED LEARNING CALCULUS 1 (Proceedings of the International Conference on Future of Education, 2025)
University students have adopted various strategies to learn Calculus 1, especially during the pandemic era when digital technology became integral to their learning processes. This study aims to explore how university students leverage digital technology to engage in self-regulated learning (SRL) while studying Calculus 1. A qualitative research approach was employed, focusing on university students who completed the course through online learning. Six participants were interviewed to gather insights into their use of digital tools for learning regulation. The findings reveal that communication tools such as WhatsApp, Microsoft Teams Chat, and email are commonly used by students to seek social support, share information, and keep each other informed about schedules, assignments, and assessments. Online conference platforms, such as Zoom and Microsoft Teams, are employed for group discussions, particularly to clarify concepts and address doubts about complex topics. Students also regulate their learning by organizing and compiling study materials through online storage services like Google Drive. This allows them to access their resources efficiently and maintain a structured approach to studying. Furthermore, students utilize open resource technologies such as Desmos, GeoGebra, and online scientific calculators to validate their answers and visualize mathematical concepts. These tools help students deepen their understanding of Calculus 1 by enabling interactive exploration and immediate feedback. This study underscores the significance of digital technology in facilitating SRL among university students. By effectively incorporating digital tools into their learning strategies, students can adapt to online learning environments and enhance their engagement with challenging subjects like Calculus 1.
Keywords: SRL strategies; learning calculus; digital technology; Calculus 1; qualitative research; online learning